Vibrationally Induced Photophysical Response of Sr2NaMg2V3O12:Eu3+ for Dual‐Mode Temperature Sensing and Safety Signs. Issue 6 (26th August 2021) - Bindhu, Amrithakrishnan; Naseemabeevi, Jawahar I.; Ganesanpotti, Subodh
Abstract : In the dual‐emitting Eu 3+ ‐activated Sr2 NaMg2 V3 O12 garnet, vibrationally induced thermometric response and thermochromic luminescence are investigated for the first time. Based on the diverse thermal quenching of VO4 3− and Eu 3+ along with the advantage of variation in the fluorescence intensity ratio, a potential phosphor for sensitive dual‐mode ratiometric and colorimetric temperature sensors is proposed in which maximum absolute and relative sensitivity of 0.0135 K −1 and 1.61% K −1 are obtained at 420 K with a temperature resolution <0.2 K. Efficient thermochromic luminescence in which colorific shift from white (300 K) to red (500 K) is observed such that the requirement of larger number of phonons weakens the nonradiative relaxation of Eu 3+, resulting in slow quenching, substantiated by estimating radiative and nonradiative decay rates by the 4f–4f intensity method. In contrast, a strong vibrational coupling of excited electrons of the VO4 3− complex is identified and verified by means of temperature‐dependent Raman and photoluminescence excitation spectra for the first time. Consequently, an increased thermal population of vibrational levels favors rapid thermal quenching of luminescence of VO4 3− via crossover mechanism. Hence dual‐centered Sr2 NaMg2 V3 O12 :Eu is an efficient thermometric and thermochromic luminescent material for optical thermometry and safety sign applications in a high‐temperature environment. Abstract : Diverse thermal quenching of VO4 3− and Eu 3+ in Sr2 NaMg2 V3 O12 :Eu phosphors displays an efficient thermometric and thermochromic response suitable for temperature sensors in ratiometric thermometry and safety signs. The fast and slow thermal quenching of VO4 3− and Eu 3+ is due to the increased cross‐over via thermal population of vibrational levels and the weak nonradiative relaxation of 5 D0 electrons, respectively.